Meningkatkan Daya Saing UMKM Wardang Melalui Strategi Pemasaran Digital - Clarrise Michelle Effendi; Shakila Nur Azzah Afifa; Elsa Anna Natasya; Vanessa Elvaretta; Vanessa Augustin; Yeremias David Satya; Delvin Brelyan; Jansen Kalyano Tan; Santi Rimadias (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the Indonesian economy, but many face challenges in implementing effective marketing strategies. Wardang, a Padang cuisine business located in Tangerang Regency, shows significant growth potential but has not fully utilized digital marketing tools. This community service program aims to assist Wardang MSMEs in developing and implementing a comprehensive digital marketing strategy. Through a combination of observation, interviews, and SWOT analysis, the program identifies key areas that need improvement and provides tailored support. This includes creating engaging social media content, developing digital menus, and building custom service websites. This initiative has succeeded in expanding Wardang's market reach, increasing its digital visibility, and strengthening its competitiveness in the market.